Caryophyllaeid cestode infestations in Clarias batrachus (Linn., 1758) in Mymensingh region (Journal of the Bangladesh Agricultural University, 2012)
Investigation was conducted on seasonal infestations of caryophyllaeid cestodes in Clarias batrachus of Mymensingh from August 2010 to July 2011. Host fish were collected for examination from different sources of water bodies and fish markets of Mymensingh. Five different parasite species- Djombangia peretrans, Lytocestus indicus, L. birmanicus, L. parvulus and Bovienia serialis were recorded. Percent of   infestations was 85.75 with 7.37 parasites per infested host. The prevalence was (100%) in December, April, June, August and September and the lowest (33%) in July. The maximum mean intensity (25.94) was found in December and the minimum (1.5) in May. The highest prevalence was observed in winter  season and the lowest was in rainy season. Index of infection and abundance were the highest in winter and the lowest in rainy season.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11051   J. Bangladesh Agril. Univ. 9(2): 351357, 2011